Risk Factors for Peripheral Vertigo - Yuni Retno Sekarwangi; Dwi Marliyawati; Kanti Yunika; Zulfikar Naftali (RSUP Dr. Kariadi, 2024)
Background: Several risk factors influence the occurrence of peripheral vertigo, including advanced age, gender, and chronic metabolic diseases. This disease is not widely recorded in primary care due to the need for detection with simple examinations. Research on the association of several risk factors has yet to be reported. Objectives: To examine the relationship between age, gender, type 2 diabetes mellitus (DM2), and hypertension as risk factors for peripheral vertigo. Methods: This study is a case-control study that used consecutive sampling. The study sample consisted of 39 people: 19 in the case group and 20 in the control group. Data were obtained from 2 health centers and Diponegoro National Hospital, Semarang City. The data were obtained from history taking and physical examinations such as the Gans Sensory Organization Performance Test (SOP), past pointing test, and dysdiadokokinesia test. DM2 disease and hypertension were gathered from medical records. Data analysis used univariate analysis, bivariate analysis with chi-square, and logistic regression multivariate analysis. Results: Statistical test results concluded that hypertension is a risk factor for peripheral vertigo (p = 0.008; OR = 6.964; 95%CI = 1.657 - 29.263). Whereas age, gender, and DM2 were not risk factors, with p-values of 0.187, 0.378, and 0.417, respectively. Conclusion: The significant risk factor associated with the occurrence of peripheral vertigo was hypertension by 6.964 times.